"Liber registri Didaci secundi". On the Medieval Manuscript Tradition of the "História Compostelana" - Souto Cabo, José António (Madrygal. Revista de Estudios Gallegos, 2018)
This paper analyzes the previous proposals concerning the genealogical links between the different medieval manuscripts of the História Compostelana, in particular as regards the relationship between the S codex (Library of the University of Salamanca) and P (Pontevedra Museum). Through a contrastive analysis of these testimonies, which also includes manuscript A (Archive of the Cathedral of Santiago), we have come to infer with some certainty that the P codex is a copy of S. This conclusion, based on a copious set of data, diverges from a hypothesis that deemed them independent in their relationship with a common previous testimony and has an important meaning for the critical establishment of the text of the work in question.
Keywords: Textual Criticism; História Compostelana; History of Galiza; Santiago de Compostela; Archbishop Diogo Gelmires.